2013
DOI: 10.1128/aac.01484-13
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacies of Amphotericin B, Posaconazole, Voriconazole, and Anidulafungin in a Murine Disseminated Infection by the Emerging Opportunistic Fungus Sarocladium (Acremonium) kiliense

Abstract: We evaluated and compared the efficacies of different antifungal drugs against Sarocladium kiliense (formerly Acremonium kiliense), a clinically relevant opportunistic fungus, in a murine model of systemic infection. Three clinical strains of this fungus were tested, and the therapy administered was as follows: posaconazole at 20 mg/kg of body weight (twice daily), voriconazole at 40 mg/kg, anidulafungin at 10 mg/kg, or amphotericin B at 0.8 mg/kg. The efficacy was evaluated by prolonged animal survival, tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
6
0
1
Order By: Relevance
“…It is of note that most treatment in the reviewed cases was based on AMB therapy (Table 1), which contrasts with the available in vitro susceptibility data, 1,8,26,148,149 and also with the in vivo data retrieved from murine models, in which, very interestingly, PSC and the combination AFG + PSC were the treatments with the most favourable outcomes. 154,155 However, according to most of the cases summarised in this review, VRC-based therapy together with, if necessary, surgical debridement is the most likely successful treatment when initiated early.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of note that most treatment in the reviewed cases was based on AMB therapy (Table 1), which contrasts with the available in vitro susceptibility data, 1,8,26,148,149 and also with the in vivo data retrieved from murine models, in which, very interestingly, PSC and the combination AFG + PSC were the treatments with the most favourable outcomes. 154,155 However, according to most of the cases summarised in this review, VRC-based therapy together with, if necessary, surgical debridement is the most likely successful treatment when initiated early.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding in vivo antifungal studies, monotherapies consisting of PSC, VRC, AFG or AMB as well as combined treatments of AFG + PSC, AFG + VRC and AMB + VRC against experimental infections have been tested against A kiliense in a murine model and compared to in vitro data 154,155 . In this case, although PSC was inactive in the in vitro setting, treatment with this drug in mice showed the best efficacy among the antifungals tested.…”
Section: Antifungal Susceptibility Testingmentioning
confidence: 99%
“…Traditionally, species of Sarocladium have been reported as plant pathogens or as saprobes ( Gams & Hawksworth 1975 , Chen et al 1986 , Helfer 1991 ). However, numerous recent studies have demonstrated that some might also be involved in human infections ( Das et al 2010 , de Hoog et al 2011 , Khan et al 2011 , Perdomo et al 2011 , Summerbell et al 2011 , Fernández-Silva et al 2013 , Júnior et al 2013 , Sharma et al 2013 ). Specifically, the new species described here, i.e., S. bifurcatum , S. hominis , S. pseudostrictum and S. subulatum , were isolated from human samples.…”
Section: Discussionmentioning
confidence: 99%
“…A pesar del alto número de casos identificados, no se registraron fallecidos con letalidad causada por la infección y sólo en uno de los dos fallecidos la auditoría realizada por médicos locales estimó que la infección pudo contribuir al fallecimiento, sin ser la causa de ella. Esta situación pudo asociarse a una baja virulencia del hongo, a pesar de tratarse de una población mayoritaria con inmunocompromiso y a la alta resistencia encontrada a los tratamientos antifúngicos, reflejada en las elevadas CIMs a los distintos compuestos antifúngicos estudiados, resultado consistente con otras publicaciones 12, 21 .…”
Section: Discussionunclassified